Kontekstualisasi Objek Zakat Era Kontemporer di Indonesia: Aset Keuangan Publik Dalam Pembangunan Bangsa - Maulana, Nora; Satibi, Ibi (Jurnal Iqtisaduna, 2024)
The sharpness of ijtihad studied by Islamic scholars has succeeded in opening up space for the interpretation of zakat objects which were initially understood traditionally in a narrow scope but now there are various contextualizations of obligatory zakat objects into several new sub-categories through a broader review and are able to represent the current state of society. This article attempts to explore the essence and contextualization of zakat objects in the contemporary era as public financial assets in nation building. The research adopted a descriptive qualitative method through a Systematic Literature Review (SLR) approach. Information and data collection is carried out using documentation techniques, while data analysis is carried out through three reviews, namely data reduction, data presentation and drawing conclusions. Indonesia has a lot of contextualization of contemporary zakat objects, starting from professional or income zakat objects, corporate zakat, stock and bond zakat, investments and deposits, mutual fund zakat, including content creator zakat which has emerged along with technological developments and changes in lifestyle trends. This potential is also supported by Indonesia’s population, which is predominantly Muslim, reaching 237.55 million people or 86.7% in 2023. With so many obligatory zakat objects and a high Muslim population, these two potentials, if managed and utilized properly, can provide positive impact in reducing economic disparities, realizing prosperity, and accelerate national development.